Pig manure management practices in South-East Benin (West-Africa) - ADJOLOHOUN, SÉBASTIEN (My University, 2023)
The aim of this study was to investigate pig manure use practices on pig farms in Benin. Data on the socio-economic characteristics of the farmers, herd structure and pig manure management practices were collected using a structured questionnaire. It was addressed to one hundred fifty-seven (157) randomly selected pig farmers in the departments of Ouémé and Plateau in south-eastern Benin. The data were analyzed using descriptive statistics and multinomial logit model. Results showed that majority of the farmers (55 %) used pig manure burial. Complaints about poor manure management were the reason for the change of site, 82.9% in Ouémé and 78.3% in Plateau (p-value > 0.05).
Keywords: Pig; manure management techniques; environment; pig farmers; Benin.